Barrett's esophagus: Proton pump inhibitors and chemoprevention I - Triadafilopoulos, George; Taddei, Antonio; Bechi, Paolo; Freschi, Giancarlo; Ringressi, Maria Novella; Degli'Innocenti, Duccio Rossi; Castiglione, Francesca; Masini, Emmanuella; Majewski, Marek; Wallner, Grzegorz; Sarosiek, Jerzy; Dillon, John F.; et al. (Blackwell Publishing Inc., 2011)
The following on proton pump inhibitors and chemoprevention in Barrett's esophagus includes commentaries on normalization of esophageal refluxate; the effects of 5-HT4 agonists on EGF secretion and of lubripristone on chloride channels agents; the role of Campylobacter toxin production; the deleterious effects of unconjugated bile acids; the role of baclofen in nonacid reflux; the threshold for adequate esophageal acid exposure; the effects of proton pump inhibitor (PPI) therapy on normalization of esophageal pH and on cell proliferation; the role of the phenotype of cellular proliferation on the effects of PPI therapy; and the value of Symptom Index and Symptom Association Probability in the evaluation of potential response to treatment. © 2011 New York Academy of Sciences.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Antireflux surgery; Baclofen; Barrett's cell lines; Barrett's treatment; Basal cell layer; Campylobacter; CDX2; Duodenogastroesophageal reflux; Dysplasia; EGF; Esomeprazole; GERD; Hyperplasia; Lesogaberan; Microbiota; Mucin phenotype; Mucosal protection; Omeprazole; PH control; PPI; Prostone; Stromal papillae; Symptom Association Probability; Symptom Sensitivity Index; TGF-α; TLESR; Weakly acidic reflux